Court-annexed mediations within Singapore: A complex interface between individual place and the court environment - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2018)
The concept of the multi-door courthouse emerged in 1976, and many judiciaries now have court-connected mediation programs. Situating dispute resolution services within the courts raises intriguing issues concerning the juxtaposition of adjudicatory and consensual communication processes. Does the convergence of litigation and mediation within the court setting have a discernible impact on the conflict being mediated? Quek Anderson addresses this question by examining the court environment as a ‘place’ and its effect on the participants’ communication patterns and the dynamics of a dispute. This chapter distils learning points from case studies drawn from Quek Anderson’s experience of mediating in the Singapore courts. It suggests how mediators in court settings can use these observations to assist in the effective resolution of disputes.